Introduction to computer organization : an under-the-hood look at hardware and x86-64 assembly - Plantz, Robert G. (San Francisco : No starch press, 2022)
Introduction to Computer Organization gives programmers a practical understanding of what happens in a computer when you execute your code. Working from the ground up, the book starts with fundamental concepts like memory organization, digital circuit design, and computer arithmetic. It then uses C/C++ to explore how familiar high-level coding concepts$1 (Blike control flow, input/output, and functions$1 (Bare implemented in assembly language. The goal isn$1 (Bt to make you an assembly language programmer, but to help you understand what happens behind the scenes when you run your programs.s
Introduction -- Chapter 1: Setting the Stage -- Chapter 2: Data Storage Formats -- Chapter 3: Computer Arithmetic -- Chapter 4: Boolean Algebra -- Chapter 5: Logic Gates -- Chapter 6: Combinational Logic Circuits -- Chapter 7: Sequential Logic Circuits -- Chapter 8: Memory -- Chapter 9: Central Processing Unit -- Chapter 10: Programming in Assembly Language -- Chapter 11: Inside the main Function -- Chapter 12: Instruction Details -- Chapter 13: Control Flow Constructs -- Chapter 14: Inside Subfunctions -- Chapter 15: Special Uses of Subfunctions -- Chapter 16: Bitwise Logic, Multiplication, and Division Instructions -- Chapter 17: Data Structures -- Chapter 18: Object-Oriented Programming -- Chapter 19: Fractional Numbers -- Chapter 20: Input/Output -- Chapter 21: Exceptions and Interrupts -- Index.
Includes index.
Keywords: COMPUTER SCIENCE; DATA STRUCTURES